Effectiveness of learning and motivation to use google classroom on critical thinking skills - Herlina, Meti; Syahfitri, Jayanti (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2022)
The effectiveness of learning is said to be successful if all learning can be fulfilled. One of them is learning motivation. Learning that can increase the effectiveness of learning and student motivation towards critical thinking skills is electronic learning with the google classroom application. E-learning can measure students' motivation to learn and their critical thinking skills. Students are considered successful when they achieve their learning goals. But in reality, students havenot shown motivation and critical thinking skills. This is what makes learning activities less effective and efficient. Students tend to be lazy to think and express their opinions. During the learning process, students need to be motivated to be interested in learning, thinking and understanding the material. It is the responsibility of the lecturer to always innovate in the learning process in order to stimulate motivation and critical thinking skills. The purpose of this study was to determine whether there was an effect of learning effectiveness and motivation using google classroom on critical thinking skills in educational research methods courses. This type of research is a quasi-experimental research (quasi experimental). The design used is the non-equivalent group design. The research population was all students of the fifth semester of Biology Education, which amounted to 65 students which were divided into 2 classes, while the sample was class A, which amounted to 35 people. The method of collecting data on the effectiveness of learning and motivation uses a questionnaire while the ability to think critically uses a test. Then the data were analyzed using the ANACOVA test. Based on the results of the research through the ANACOVA test, it can be concluded that the effectiveness of learning and motivation using google classroom has an influence on the critical thinking skills of the fifth semester students of FKIP UMB for the 2020/2021 academic year.